The influence of entertainment and brand characters on children's object preferences and monetary judgments - Williams-Gant, Allison J.; Harden, Isabelle; Corriveau, Kathleen H. (Frontiers in Developmental Psychology, 2024)
Companies often use images of popular characters from children's media on their products. The current study investigated how different types of popular characters (i.e., entertainment or brand) influence children’s trust, preference for, and monetary judgments of objects. Additionally, we explored whether children’s own parasocial relationships with such characters influence their preferences and judgments. Participants included 66 four- and five-year-olds (Mage = 5.06; SD = 0.48; 34 boys; 32 girls). First, children completed a selective trust task measuring their preference for information from a familiar or unfamiliar character. Then children asked which object (i.e., damaged with a familiar character image or undamaged without a familiar character image) they would want and which people would pay more money for. Results indicated regardless of character type (i.e., entertainment or brand), children did not trust (i.e., seek out new information or endorse specific testimony) the familiar marketing character more than an unfamiliar character. Children across all character conditions did not display a preference for either object, however they were more likely to rate the undamaged object as more valuable than the damaged object featuring the familiar character. Parasocial relationships for all types of characters were high and did not relate to children’s preferences or judgments. These findings expand on previous research suggesting that although the presence of familiar media characters can influence children’s preferences for individual objects, children can also weigh more relevant features of an object, such as potential flaws in the design, when making other decisions (e.g., value).